Comparison of the Efficacy of Cognitive Behavioral Therapy and Eye Movement Desensitization and Reprocessing (EMDR) on the Quality of Life in Adolescents with Social Anxiety Disorder - Moghbeli, Farnaz; Bahrami, Mohsen; Jafari, Davood (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The aim of this study was to compare the effectiveness of Cognitive Behavioral Therapy (CBT) and Eye Movement Desensitization and Reprocessing (EMDR) on quality of life in adolescents diagnosed with social anxiety disorder in Karaj.Methods and Materials: The research methodology was a quasi-experimental pretest-posttest design with a control group and a one-month follow-up. The sample included all adolescents visiting the Cultural Clinic in Karaj from February 2021 to May 2021, who were definitively diagnosed with social anxiety disorder by a psychiatrist. Fifty-one individuals were purposively selected and randomly assigned into two experimental groups and one control group (each group consisting of 17 participants). The first and second experimental groups underwent 12 and 8 sessions of CBT and EMDR respectively. The World Health Organization Quality of Life-BREF (WHO-QOL-BREF, 1996) questionnaire was used as the measurement tool. Data analysis was conducted using repeated measures analysis of variance and Bonferroni tests.Findings: Results indicated that both CBT and EMDR interventions significantly improved quality of life scores compared to the control group (p < 0.001), and this effectiveness was maintained during the one-month follow-up period. There was no significant difference between the effectiveness of the two intervention methods in improving quality of life scores (p < 0.001).Conclusion: Therefore, using CBT and EMDR can significantly enhance the quality of life in adolescents suffering from social anxiety disorder.